2006
DOI: 10.1021/ol0602295
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Practical Instant Catalyst for Cyclotrimerization of Alkynes to Substituted Benzenes

Abstract: [reaction: see text] A 2-(2,6-diisopropylphenyl)iminomethylpyridine (1a)/CoCl(2).6H(2)O/Zn reagent has been developed as an effective instant catalyst for the intra- and intermolecular cyclotrimerization of alkynes to substituted benzenes, making the method extremely practical since the reagent, 1a/CoCl(2).6H(2)O/Zn, is inexpensive and easy to handle and the reaction is less sensitive to moisture and is reasonably general.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(38 citation statements)
references
References 13 publications
2
36
0
Order By: Relevance
“…on reaction efficiency and selectivity, [11] the reason why silver salts other than AgOTf and AgSbF 6 were less effective in the present catalysis is unclear at this stage.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…on reaction efficiency and selectivity, [11] the reason why silver salts other than AgOTf and AgSbF 6 were less effective in the present catalysis is unclear at this stage.…”
Section: Resultsmentioning
confidence: 84%
“…Addition of AgOTf (4 mol %) to a reduced amount of the catalyst (dipimp/CoCl 2 ·6 H 2 O/Zn = 2/2/10 mol %) was also effective (entry 6). Other silver salts such as AgBF 4 and AgPF 6 were not effective and, in fact, slowed down the reaction rate (entries 8 and 9). Addition of ZnI 2 [4] to a dipimip/CoCl 2 ·6 H 2 O/Zn system resulted in no effect (entry 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkyne [2 1 2 1 2] Cycloaddition Reaction [15,23] In connection with our research program of catalytic cycloaddition reactions, [33] at an early stage of the present study, the intramolecular [2 1 2 1 2] cycloaddition of 1,6,11-triynes, mediated by the divalent titanium reagent Ti(O-i-Pr) 4 /2i-PrMgCl, was investigated (Scheme 18 and Table 5). At the time, we sought to develop a similar reagent system with a reductant other than an organometallic agent such as i- PrMgCl, which led us to the discovery of the present reagent system.…”
Section: Bond-forming Reactionsmentioning
confidence: 99%
“…Based on our results of developing a highly practical procedure for synthesizing substituted benzenes by the [2 + 2 + 2] alkyne-cyclotrimarization which is catalyzed by a CoCl 2 -6H 2 O/Zn reagent in the presence of an appropriate ligand, 8 we planned a two-step preparation of benzyl aldehydes 1, which are the substrate of Bradsher-type cyclization/aromatization reaction, by the cycloaddition of diynes 3 and 4-aryl-2-butyn-1-ols 4 and the following oxidation (Scheme 1). We have shown that the propargyl alcohols 4 are good substrate for the selective crosscoupling with diynes 3, owing to their coordination effect of the propargyl oxygen to the metal center in an active catalyst.…”
Section: Synthesis Of Substituted Anthracenes Pentaphenes and Trinapmentioning
confidence: 99%